2020
DOI: 10.1155/2020/8867809
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Mechanical Characteristics and the Failure Mechanism of Coal‐Rock Composite under Uniaxial Load

Abstract: Due to the influence of the component structure and combination modes, the mechanical characteristics and failure modes of the coal-rock composite show different characteristics from the monomer. In order to explore the effect of different coal-rock ratios on the deformation and the failure law of the combined sample, the RMT rock mechanics test system and acoustic emission real-time monitoring system are adopted to carry out uniaxial compression tests on coal, sandstone, and three kinds of combined samples. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Zhan et al [4] defined and derived the relative physical mechanical parameters of coalrock assemblages (CRCB) to illustrate and analyze the effects of coal-rock height ratio (CRHR), coalrock body behavior and interface parameters on the CRCB. Yang et al [5] conducted uniaxial compression tests on coal, sandstone and three composite specimens using the RMT rock mechanics test system and acoustic emission real-time monitoring system, combining the evolution laws of fractal and acoustic emission signals, and investigated the crack extension and damage mechanism of the composite specimens. Bao Pan et al [6] studied the deformation characteristics and loading damage laws of coal-rock assemblages under different coal-rock height ratios based on uniaxial loading and uniaxial cyclic loading tests.…”
Section: Introductionmentioning
confidence: 99%
“…Zhan et al [4] defined and derived the relative physical mechanical parameters of coalrock assemblages (CRCB) to illustrate and analyze the effects of coal-rock height ratio (CRHR), coalrock body behavior and interface parameters on the CRCB. Yang et al [5] conducted uniaxial compression tests on coal, sandstone and three composite specimens using the RMT rock mechanics test system and acoustic emission real-time monitoring system, combining the evolution laws of fractal and acoustic emission signals, and investigated the crack extension and damage mechanism of the composite specimens. Bao Pan et al [6] studied the deformation characteristics and loading damage laws of coal-rock assemblages under different coal-rock height ratios based on uniaxial loading and uniaxial cyclic loading tests.…”
Section: Introductionmentioning
confidence: 99%
“…Zhan et al 4 defined and derived the relative physical and mechanical parameters of coal–rock combinations (CRCB) to analyze the effects of coal–rock height ratio (CRHR), coal–rock body behavior and interface parameters on the CRCB. By using the RMT rock mechanics test system and acoustic emission real-time monitoring system to combine the evolution laws of fractal and acoustic emission signals, Yang et al 5 conducted uniaxial compression tests on coal, sandstone, and three composite specimens and investigated the crack extension and damage mechanism of the composite specimens. Based on uniaxial loading and uniaxial cyclic loading tests, Bao Pan et al 6 studied the deformation characteristics and loading damage laws of coal–rock combinations under different coal–rock height ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [28] found that there is a critical loading rate in the uniaxial compression mechanical test of the coal-rock combined body in the range of the low loading rate, and the coal-rock combined body has different mechanical properties in a certain range on both sides of the critical loading rate. Yang et al [29] concluded that, with the increase in the impact velocity, the maximum dynamic peak stress and peak strain of the coalrock combined body have an obvious strain rate effect, and the maximum dynamic peak stress increases as an approximate power function. Ma et al [30] found that the uniaxial compressive strength and elastic modulus of coal-rock combined specimens increase with the increase in the loading rate.…”
Section: Introductionmentioning
confidence: 99%